2015
DOI: 10.1128/jcm.01385-15
|View full text |Cite
|
Sign up to set email alerts
|

Limited Variation in BK Virus T-Cell Epitopes Revealed by Next-Generation Sequencing

Abstract: f BK virus (BKV) infection causing end-organ disease remains a formidable challenge to the hematopoietic cell transplant (HCT) and kidney transplant fields. As BKV-specific treatments are limited, immunologic-based therapies may be a promising and novel therapeutic option for transplant recipients with persistent BKV infection. Here, we describe a whole-genome, deep-sequencing methodology and bioinformatics pipeline that identify BKV variants across the genome and at BKV-specific HLA-A2-, HLA-B0702-, and HLA-B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 40 publications
(48 reference statements)
1
10
0
Order By: Relevance
“…Using this highly innovative approach, Cioni et al successfully expanded the list of BKV T cell epitopes to at least 39, among which 21 epitopes were further confirmed by HLA peptide streptamer staining (105). Sahoo et al assessed genetic variability in sections of the BKV genome coding for T cell epitopes, demonstrating very limited variability (less than 5%) in a cohort of 65 samples (106). Cioni and colleagues demonstrated that some of the epitopes they identified shared strong homology with JC polyomavirus (JCV) (105).…”
Section: Adaptive Immune Responsementioning
confidence: 99%
“…Using this highly innovative approach, Cioni et al successfully expanded the list of BKV T cell epitopes to at least 39, among which 21 epitopes were further confirmed by HLA peptide streptamer staining (105). Sahoo et al assessed genetic variability in sections of the BKV genome coding for T cell epitopes, demonstrating very limited variability (less than 5%) in a cohort of 65 samples (106). Cioni and colleagues demonstrated that some of the epitopes they identified shared strong homology with JC polyomavirus (JCV) (105).…”
Section: Adaptive Immune Responsementioning
confidence: 99%
“…After exclusion of 231 articles based on title and abstract for clearly not fulfilling inclusion criteria due to type of article, study design, population or outcome of interest, and 47 articles excluded due to being duplicates, 71 articles were left for full‐length review. Subsequently, 63 articles were additionally excluded (25 articles did not report the outcome of interest; 17 were not observational studies; and 21 articles were excluded because they were from countries outside the United States and/or consisted of a pediatric population). Thus, eight observational studies with a total of 193 samples (urine, blood, and kidney tissues) from 188 BKV‐infected KTX adult recipients in the United States were enrolled.…”
Section: Resultsmentioning
confidence: 99%
“…This factor is involved in a complex regulatory pathway that can affect the course of BKV infection[ 375 ]. The genetic variation of BKV strains is limited[ 425 ]. In HLA-A*0201 individuals, cytotoxic T-cell lymphocyte (CTL) responses are elicited towards two of the VP1 epitopes, VP1(p44) and VP1(p108)[ 347 ].…”
Section: Pathogenesis Of Bkv Infection[ 10 mentioning
confidence: 99%